Effects of different dialysis methods on cardiac structure and function of uremic patients - HUANG Ya-qing; YU Guo-qing; WANG Qiang; LIN Qiang; ZHUANG Yong-ze (Linchuang shenzangbing zazhi)
Objective To investigate the influence of different dialysis methods on cardiac structure and function in patients with uremia,and to study the related influencing factors.Methods The patients(n=63)who had received dialysis in Nanjing General Hospital of Fuzhou Military from 2012 to 2015 were selected and divided into peritoneal dialysis(PD)group(n=32)and hemodialysis(HD)group(n=31).The cardiac ultrasound examination was performed before and after dialysis in both two groups.The general information,as well as echocardiography indexes including IVST,LVWPT,LVDd,LAD and LVEF was collected.The left ventricular mass index(LVMI) was calculated.The differences between the groups before and after dialysis were compared,and the related influencing factors were analyzed.Results The general information of two groups had no significant difference.After dialysis the urine volume in PD group was greater than in HD group,but there was no significant difference before the dialysis.There was no significant difference between the two groups in cardiac indexes before dialysis.After dialysis,the LVMI in two groups was significantly increased than before dialysis(P<0.05).LVMI,IVST and LVWPT were significantly increased in HD group as compared with those in PD group.LVMI was positively related with systolic blood pressure(r=0.382,P<0.05),and negatively with hemoglobin,LDL and residual urine volume(r=-0.303,-0.253,-0.4;P<0.05 or P<0.01,respectively).Conclusions Dialysis can affect the cardiac structure and function in patients with uremia,and HD may be grater,which may be related to residual renal function,blood pressure,anemia,LDL and other factors.This reminded us that we should early prevent and improve the cardiac function in dialysis patients.